Allosteric Regulation of the Soluble Epoxide Hydrolase by Nitro Fatty Acids: a Combined Experimental and Computational Approach. Issue 17 (15th September 2022) - Qiu, Qiongju; Abis, Giancarlo; Mattingly-Peck, Florence; Lynham, Steven; Fraternali, Franca; Conte, Maria R
Graphical abstract: Highlights: hsEH is a therapeutic target, but no approved drug is available. hsEH CTD is allosterically regulated by electrophilic fatty acids. New covalent modification sites were identified as latent allosteric sites. Distinct electrophilic fatty acids differentially modulate allosteric propagation. Allosteric inhibition strategies could circumvent limitations of orthosteric drugs. Abstract: The human soluble epoxide hydrolase (hsEH) is a key regulator of epoxy fatty acid (EpFA) metabolism. Inhibition of sEH can maintain endogenous levels of beneficial EpFAs and reduce the levels of their corresponding diol products, thus ameliorating a variety of pathological conditions including cardiovascular, central nervous system and metabolic diseases. The quest for orthosteric drugs that bind directly to the catalytic crevice of hsEH has been prolonged and sustained over the past decades, but the disappointing outcome of clinical trials to date warrants alternative pharmacological approaches. Previously, we have shown that hsEH can be allosterically inhibited by the endogenous electrophilic lipid 15-deoxy-Δ 12, 14 -Prostaglandin-J2, via covalent adduction to two cysteines, C423 and C522. In this study, we explore the properties and behaviour of three electrophilic lipids belonging to the class of the nitro fatty acids, namely 9- and 10-nitrooleate and 10-nitrolinoleate. Biochemical and biophysical investigations revealed that, in addition to C423 and C522, nitro fatty acids can covalently bind to additional nucleophilic residues in hsEH C-terminal domain (CTD), two of which predicted in this study to be latent allosteric sites. Systematic mapping of the protein mutational space and evaluation of possible propagation pathways delineated selected residues, both in the allosteric patches and in other regions of the enzyme, envisaged to play a role in allosteric signalling. The responses elicited by the ligands on the covalent adduction sites supports future fragment-based design studies of new allosteric effectors for hsEH with increased efficacy and selectivity.